(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
The purpose of this study was to analyze the effectiveness of using the role-playing learning model in improving student learning activities in Social Studies (IPS) at the elementary school level. This study employed a qualitative method with a literature review, which involved analyzing and summarizing various relevant research findings. The data used were secondary data taken from scientific journal articles published between 2020 and 2026, through academic platforms such as Google Scholar. The article selection process was carried out based on certain criteria to obtain 10 articles that matched the research focus. To analyze the data, a qualitative descriptive analysis was used through steps such as identification, selection, assessment, and integration of findings. The results of this study indicate that the role-playing learning model is very effective in improving student learning activities, as evidenced by increased student participation, interaction, and engagement during the learning process. Furthermore, this model also helps improve collaboration, conceptual understanding, and student learning outcomes. This effectiveness is supported by the characteristics of the role-playing model, which makes students the main actors in the learning process. Thus, the role-playing learning model can be an alternative learning strategy that can improve the activity and quality of social studies learning in elementary schools.